Cleft Nasal Deformity And Rhinoplasty; Review Article (Journal of Pharmaceutical Negative Results, 2023)
Even for a highly skilled plastic surgeon, managing cleft-lip and nasal deformity is challenging. the deformity may be mostly addressed early at the time of cleft lip repair or later by secondary rhinoplasty procedure. However, it's crucial to remember that the severity of the abnormality, the consequences of growing through time, and the aftereffects of earlier surgery's scarring might influence the outcomes of secondary cleft nasal repair. Primary, intermediate, and secondary or final repairs may be categorized according to the time of surgical intervention for correction of cleft lip nasal deformity. The primary cleft rhinoplasty is commonly performed at 3 months of age along with primary cheiloplasty. Intermediate rhinoplasty is referred as interventions that carried out before nose growth is complete, between definitive lip repair and secondary rhinoplasty. Once the maxillary and nasal development stops, which is around the ages of 14 to 16 for girls and 16 to 18 for boys, secondary or definitive rhinoplasty is performed. As a result, there is still no agreement on the best method, and the final aesthetics of cleft restoration are still hindered by the cleft nose. But for many, achieving total rectification of all nasal defects remains a distant dream.